Multiple AGN activity during the BCG assembly of XDCPJ0044.0-2033 at z ∼ 1.6. Issue 2 (19th August 2020) - Travascio, A; Bongiorno, A; Tozzi, P; Fassbender, R; De Gasperin, F; Cardone, V F; Zappacosta, L; Vietri, G; Merlin, E; Bischetti, M; Piconcelli, E; Duras, F; et al.
ABSTRACT: Undisturbed galaxy clusters are characterized by a massive and large elliptical galaxy at their centre, i.e. the brightest cluster galaxy (BCG). How these central galaxies form is still debated. According to most models, a typical epoch for their assembly is $z$ ∼ 1–2. We have performed a detailed multiwavelength analysis of the core of XMM–Newton Distant Cluster Project (XDCP) J0044.0-2033 (XDCP0044 ), one of the most massive and densest galaxy clusters currently known at redshift $z$ ∼ 1.6, whose central galaxy population shows high star formation compared to lower z clusters and an X-ray active galactic nuclei (AGN) located close to its centre. SINFONI J -, H -, and KMOS YJ -, H -bands spectroscopic data have been analysed, together with deep archival HST photometric data in F105W, F140W, and F160W bands, Chandra X-ray, radio JVLA data at 1–2 GHz, and ALMA band-6 observations. In the very central region of the cluster (∼70 kpc × 70 kpc), two systems of interacting galaxies have been identified and studied (Complex A and B ), with a total of seven confirmed cluster members. These galaxies show perturbed morphologies and three of them show signs of AGN activity. In particular, two type-1 AGN with typical broad lines have been found at the centre of each complex (both of them X-ray obscured and highly accreting with $\rm λ _{Edd}\sim 0.4-0.6$ ), while a type-2 AGN has been discovered in Complex A. The AGN at the centre of Complex B is also detected in X-ray, while the other two are spatially related to radio emission. The three AGN provide one of the closest AGN triple at $z$ > 1 revealed so far with a minimum (maximum) projected distance of 10 (40) kpc. The observation of high star formation, merger signatures, and nuclear activity in the core of XDCP0044 suggests that all these processes are key ingredients in shaping the nascent BCG. According to our data, XDCP0044 could form a typical massive galaxy of $M_{\star }\sim 10^{12} \, M_{\odot }$, hosting a black hole of $\rm 2 × 10^8\!-\!10^9 \, M_{\odot }$, in a time-scale of the order of ∼2.5 Gyr.